An Analysis of Students’ Difficulties in Pronouncing English Dipthong at The Twelve Grade of SMA Negeri 8 Jambi City - Riyanda Tri Hardi; Efa Silfia; Ridho Praja Dinata (JELT: Journal of English Language Teaching, 2022)
This research was aimed to find out the students difficulties and factor causes students difficult to pronounce English diphthongs at the Twelve Grade of SMA Negeri 8 Kota Jambi. The research methodology of this study was quantitative descriptive research which involved population and sample. The total population of this research was the XII IPS 5 students of SMAN 8 Kota Jambi, which consisted of 42 students. In collecting the data, this research gave test and interview at the class. The result of the research showed that the twelve grade students of SMA Negeri 8 Kota Jambi got difficulties in pronouncing English diphthongs sounds. The students’ difficulties in pronouncing diphthongs are producing sound (/ʌʊ/, /eə/, and /ɪə/). The highest percentage of the students score was 95,23% and the lowest was 15,23%. Where the mean score of the students test was 10 with a poor categories and percentage of students score test were /ʌʊ/ 15,23%, /eə/ 16,19%, and /ɪə/ 17,14%. The factors of students’ difficulties in pronouncing English fricative consonant are; the influence of students mother language, the lack of students knowledge about English sound system and the unsuccessful in using borrowed English words.